THE EFFECTIVENESS OF USING RECIPROCAL TEACHING TECHNIQUE IN TEACHING DESCRIPTIVE TEXT AT SECOND GRADE ENGLISH DEPARTMENT - Kinanatul Fajariyah; Evha Nazalatus Sy (The Ellite of Unira, 2022)
English is very important for communication. People can express their ideas to communicate. Communication speaks with others. It means that language should be learned by people around the world. Reading is one of the daily activities in human life. Teaching reading English can improve the other skills especially for listening, writing, and speaking. The purpose of reading is to help the reader comprehend the text. In addition, reading gives someone for information and for pleasure. This study is aimed at finding is the effectiveness of using Reciprocal Teaching in teaching descriptive text at the second grade English Department of Madura University in the academic year of 2020/2021. Reciprocal Teaching has four techniques. They are predicting, questioning, clarifying, And summarizing. The researcher used quantitative research, one group pre-test post-test . The population of this research is all students of the English department Of Madura University. The sample was one class; the Second grade of the English department. To analyzing the data, the researcher used SPSS V.16. This research was conducted by giving a pre-test, applying an experiment using reciprocal teaching, and giving a post-test. The data were analyzed using the t-test formula to determine the effectiveness of using reciprocal teaching. The results showed that the average value of the pre-test was 47.4 then after being given the reciprocal teaching technique, the students were given a post-test with an average score of 89.9. The value of the Normality test using the reciprocal teaching technique is 0.795 > 0.05 (Asymp. Sig. (2tailed)). Then, for the significant homogeneity test 0.205 > 0.05 (Asymp. Sig. (2tailed)). Then, for the Hypothesis Test value of (0.000) < 0.005 (Asymp. Sig. (2tailed)) So there is a significant difference between learning descriptive text not using reciprocal teaching technique and descriptive text learning using a reciprocal teaching technique.